Utilization of low-grade iron ore in ammonia decomposition - Othman, Nur Ezzah Faezah; Mohd. Salleh, Hamzah; Purwanto, Hadi (Elsevier, 2016)
Due to its cleanliness, fast energy cycle, and convenience of energy conversion, hydrogen has been regarded as the new energy source. Conventional process to produce hydrogen yield large amount of CO as byproduct. Moreover, the hydrogen storage and transportation have become the drawbacks in hydrogen economy. Thus, there has been increased interest in the hydrogen transportation medium as alternatives from the conventional process to produce and transport hydrogen. Ammonia has drawn worldwide attention as the most reliable hydrogen transportation medium. Through the decomposition of ammonia, hydrogen and nitrogen gas were produces as the byproduct without any CO or CO2 emission. In this experiment, the ore were introduced as the medium for ammonia decomposition. The ore were put into quartz tube reactor and were dehydrated at 400°C for 1 hour, then hydrogen reduced for 2 hours before and undergone ammonia decomposition at 500-700°C for 3 hours. The effects of temperature to the % conversion of ammonia decomposition were also studied. Ammonia decomposition at higher temperature gives higher conversion. As seen in the results, the NH3 conversion decreased with increasing time and the value after 3 hours of reaction increased in the sequence of 500°C<600°C< 700°C. During ammonia decomposition, nitriding of iron occurred. The relation between temperature and the nitriding potential, KN is also investigated. The purpose of this study is to investigate the utilization of low-grade ore as medium for ammonia decomposition to produce hydrogen